PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PENCURIAN SECARA BERSEKUTU STUDI PUTUSAN NOMOR. 315/Pid.B/2022/PN Mre: Sentencing of Perpetrators of the Crime of Theft Jountly Study of Decision Number. 315/Pid.B/2022/PN Mre - Muhammad Ahsan Adiyatma; Dian Adriawan Tawang (Reformasi Hukum Trisakti, 2025)
Theft is a form of criminal offense often found in various mass media, both electronic and print media, which is motivated by the life circumstances of the perpetrator. The defendant Adi Candra committed the crime of theft in concert and was charged with Article 363 paragraph (1) point 4, but in PERMA Number 2 of 2012, it is included in a minor crime. The problems of this research are: How is the appropriate punishment in Decision Number 315/Pid.B/2022/PN Mre against the perpetrator of the theft crime in collaboration? Then, what is the basis for the judge's consideration in Decision Number 315/Pid.B/2022/PN Mre which decided the case with Article 363 paragraph (1) 4th of the Criminal Code? This research was conducted normatively, using secondary data, descriptive-analytical. This research result and concludes that the actions of the defendant Adi Candra are included in the class of minor crimes because the amount of loss is not more than Rp2,500,000. The judge in deciding the case was not right because it was not in accordance with applicable regulations. In handling cases, judges must reflect principles of legality and legal certainty, so that actions and facts that occur are in accordance with imposition of punishment.